(untitled) (Cultura Económica, 2019)
The paper presents an interpretation of the factors that make the clusters and agglomerations of firms emerge, and the mechanisms through which they develop and change. This question is discussed from the perspective of economic development. The paper argues that the spatial organization of production is a phenomenon associated with the economic dynamic of cities and regions and with the organization and location strategies of firms. It maintains that the development forces (diffusion of innovation, urban development and institutional change) are factors that condition the firm’s strategic decisions and so, the spatial organization of production.